SSP 2004 Proceedings of the 8th International Conference on Solid State Physics, SSP 2004, Workshop "Mössbauer Spectroscopy of Lacally Heterogeneous Systems", held in Almaty, Kazakhstan, 23-26 August, 2004 - Kadyrzhanov, K.K.; Kadyrzhanov, K.K.; Rusakov, V.S.; Rusakov, V.S. (Springer Berlin Heidelberg : Imprint: Springer, 2006)
This volume contains papers presented at the 8th International Conference on Solid State Physics (SSP 2004), Workshop "Mössbauer Spectroscopy of Locally Heterogeneous Systems", held in Almaty, Kazakhstan, 23–26 August 2004. It should be of interest to researchers and PhD students working or interested in recent results in the locally inhomogeneous system investigations by Mössbauer Spectroscopy and the new concepts of data evaluation of complex Mössbauer spectra.